An Analysis of Bank Syariah Indonesia’s Mobile Banking Services in Attracting Customers in Pandaan, Pasuruan - Aininnisa, Afidatu; Sukamto, Sukamto; Aslikhah, Aslikhah (Journal Research of Social Science, Economics, and Management, 2026)
The development of digital technology has driven the transformation of banking services, including in the Islamic banking sector through the implementation of mobile banking. This study aims to analyze the mobile banking services of Bank Syariah Indonesia (BSI) in increasing the number of customers at KCP Pandaan Pasuruan. The research method used is a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed systematically to obtain a comprehensive understanding of the implementation of digital services. The results show that BSI mobile banking services provide ease of access, time efficiency, and convenience in transactions, which positively influence public interest in becoming customers. Furthermore, features integrated with Islamic values such as ZISWAF and spiritual services offer competitive advantages that enhance customer trust and loyalty. However, several challenges remain, including uneven digital literacy, security concerns, and internet network limitations. Therefore, optimizing mobile banking services must be accompanied by digital education and system quality improvement. This study implies that sharia-based digital service innovation plays a strategic role in enhancing financial inclusion and increasing the number of customers.